Analysis of Pregnancy Anti-Discrimination Policy in Kentucky: Application of Kingdon's Multiple Streams Framework. (November 2020) - Ray, Robin
While several federal laws including the Pregnancy Discrimination Act, Family Medical Leave Act, and the Americans with Disabilities Act provide some freedom from discrimination due to pregnancy and breastfeeding-related conditions, many pregnant workers in Kentucky were not covered under these existing laws. The intent of Senate Bill 18, the Kentucky Pregnant Workers Act, was to provide clarity to employers about the protections afforded to pregnant workers by law as well as the need for employers to provide the same level of accommodations for pregnant workers that are available for those who are disabled. Similar bills had been filed during the 2015 to 2018 legislative sessions, and in 2019, Senate Bill 18 passed 87-5 and was signed by the Governor on April 9, 2019. The purpose of this article is to analyze a pregnancy anti-discrimination bill that passed during the 2019 Kentucky General Assembly utilizing Kingdon's Multiple Streams Framework. This article also contains multiple policy alternatives, interest group involvement related to pregnancy anti-discrimination policy, unintended consequences of policy implementation as well as potential issues with enforcement of the Kentucky Pregnant Workers Act.